Visualization study of a cryostat with a large diameter flow channel for flowing high-pressure cryogenic fluid. Issue 1 (1st May 2022) - Xie, S Y; Zhang, Z Z; Xu, D; Lyu, B K; Li, L F
Abstract: For abundant cryogenic experiments, systems, and so on, visualization is necessary to observe the cryogenic fluid. Therefore, the visualization methods of cryogenic fluid have been widely studied, such as shadowgraph technique, schlieren technique, and laser holographic interferometry technique. A cryostat for visualization study must have optical windows to meet the requirement of various image acquisition equipment. Due to the difference of shrinkage between transparent glass and device materials at low temperatures, especially at large diameter flow channels, it is difficult to meet the requirement of visualization. This paper studies a kind of cryogenic visualization device with an inner diameter of 200 mm, which can meet the visualization requirements of cryogenic fluid with the maximum working pressure at 0.7 MPa and the lowest temperature at 77 K. Liquid nitrogen was used to test the visualization of the device at low temperatures. The device was also subjected to vibration conditions to test the ability of the device to withstand harsh environments. The results show that the device has good sealing performance and can meet the visualization requirements well.